Market intelligence and product lifecyle management as drivers of business performance in SMEs: an absorptive capacity perspective UMKM bakso di Kabupaten Bekasi - Bintang Kusuma Dewa; Hikmatul Aulia; Mohamad Faisal (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study examines the influence of Market Intelligence (MI) and Product Lifecycle Management (PLM) on Business Performance (BP) among small and medium-sized enterprises (SMEs) in Bekasi, Indonesia, through the mediating role of Absorptive Capacity (ACAP). Using the Dynamic Capability Theory and Knowledge-Based View frameworks, the research investigates how SMEs leverage market information and product lifecycle strategies to enhance competitiveness. Data were collected from 696 SMEs across various food sectors and analyzed using Structural Equation Modeling (SEM) with AMOS 23. The findings reveal that MI significantly affects ACAP, which in turn strengthens PLM and BP. ACAP demonstrates a full mediating effect between MI and BP, indicating that market information contributes to performance only when firms possess strong absorptive capacity. Furthermore, PLM positively influences BP, confirming its role in improving operational efficiency and innovation. The study provides theoretical implications for extending ACAP applications to emerging markets and practical recommendations for SMEs to optimize market knowledge and product lifecycle management in sustaining performance.